The Influence of Concrete Resistance on the Protection of Reinforced Steel at Coastal Environment - ال الفضل الشريفة بهيجة (Latakia University Journal -Engineering Sciences Series, 2022)
The coastal areas are considered as one of the most aggressive environment to the reinforced concrete construction, the corrosion of reinforced steel leads to early deterioration in reinforced concrete and reduces its durability. The high economical cast ,which is caused by corrosion of reinforced steel in reinforced concrete constructions , made the greatest problem in the infrastructure in the industrial countries. Recently it has led to high repair costs. Sometimes exceeding the construction cost or it has led to the exit of the establishment from investment. The most harmful material to the reinforced concrete structure in the coastal environments is the penetration of chlorides into the reinforced concrete, this is why the corrosion caused by the chlorides is considered one of the most dangerous problems to those installations. The research aims to study the effect of the concrete resistance on the protection of the reinforcing steel in the reinforced concrete installation and on the bond stress between concrete and steel, through carrying out accelerated electrochemical tests and bond test of samples and finding out the result and recommendations .